ALPHA-PINENE ATTENUATES MICROGLIAL NF-ΚB ACTIVATION AND INOS EXPRESSION IN GP120-INDUCED NEUROINFLAMMATION - Rahayu, Masruroh; Widodo, M Aris; Lyrawati, Diana; Widjadjanto, Edi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Neuro-inflammation plays a role in the pathogenesis of HIV-associated dementia (HIV). Activation of microglia is essential for triggering inflammatory-mediated neurotoxicity. HIV-1 120 kDa envelope glycoprotein (gp120) induces microglial NF-κB signaling which in turn induce pro-inflammatory and iNOS gene transcription. Continuous or excessive activation of NF-κB signaling lead to persistent production of TNF-α and nitric oxide by microglia and induce neuronal apoptosis. Alpha-pinene is a natural substance found in pine tree and has efficacy on inhibiting NF-κB signaling.Objective: This study was designed as a true experimental study and aimed to investigate the effect of alpha-pinene administration toward inflammatory response represented by the percentage of microglia containing activated NF-κB and iNOS expression.Methods: Neuron-glia primary culture from brain tissue of rat fetus was divided into 5 groups as follows: negative control; positive control (gp120 1nM); treatment I, II, and III (gp120 1 nM + alpha-pinene 0.4 µg/mL, 2 µg/mL, and 10 µg/mL, respectively). Microglial NF-κB and iNOS expression were analyzed using immunohistochemistry method. Neuronal apoptosis was measured by TUNNEL method.Results: Result showed that alpha-pinene administration on gp120-treated neuron-glia at all dosages decrease NF-kB activation, iNOS expression, and apoptotic neuron significantly as compared to the gp120-only treated group (p<0.05). Furthermore, alpha-pinene did not affect NF-kB activation and neuronal apoptosis (p>0.05), but significantly elevate iNOS expression (p<0.05) mainly in dosage I and II.Conclusion: We concluded that alpha-pinene has neuroprotective effect on gp120-treated neuron-glia cells through modulation of NF-kB and iNOS expression thus inhibit neuronal apoptosis.